New perspectives in architecture through transformable structures: A simulation study - Matheou, Maria; Phocas, Marios C.; Christoforou, Eftychios G.; Müller, Andreas (Frontiers in Built Environment, 2023)
Structures enabling transformability of buildings, components and materials at different levels gain significance in view of a sustainable built environment. Such structures are capable of obtaining different shapes in response to varying functional, environmental or loading conditions. Considering certain limitations of classic tensegrity and scissor-like structures, applied so far in an architectural and engineering context, attributed to a limited number of possible configurations and a big number of actuators required, rigid-bar linkages offer a promising alternative with regard to constructability, modularity, transformability and control components integration. The paper presents two classes of a transformable spatial rigid-bar linkage structure aiming at improved flexibility and controllability with a reduced number of actuation devices. The kinematics principle is applied to a torus-shaped spatial structural system composed of planar interconnected linkages, and the reduction of each planar linkage to a one degree-of-freedom mechanism. Alternative motion sequences of multiple transformation steps can be implemented for the stepwise adjustment of the joints to their desired values. The actuators employed are positioned at the ground supports and are detached from the main structural body. Thus, minimum structural self-weight, simplicity and reduced energy consumption become possible. The transformation approaches using parametric associative design are exemplified based on a selected motion sequence pattern. The case study demonstrates the high degree of control flexibility and transformability of the system.